THE PREVALENCE OF CESAREAN AND THE EFFECTING FACTORS DURING THE COVID-19 PANDEMIC - KORUK, Fatma; TUNÇ, Ruken; UYSAL, Melisa; TURAN, Zeliha; KORUK, İbrahim (Göbeklitepe Medical Science Journal, 2022)
In terms of the clinical picture during pregnancy and perinatal outcomes, there is an insufficient amount of data in the literature regarding the effects of COVID-19 infection, which is spreading rapidly worldwide. In this study, we aimed to determine the frequency of cesarean deliveries in during the pandemic, as well as to show the effect of COVID-19 positivity and certain other variables on cesarean section delivery. The sample of this cross-sectional study consists of 956 women who gave birth in a state hospital. In this study, the prevalence of cesarean section was found to be 33.2%. Also, compared to the general population the rate of cesarean delivery was found to be 2.1 times higher in women whose incomes were less than their expenses, 2.2 times higher in those with health insurance, 13.6 times higher in those who were COVID-19 positive, and 1.6 times higher in those who did not receive regular prenatal care. This study showed that COVID-19 infection and negativities related to the social determinants of well-being significantly increased the prevalence of cesarean section during the pandemic period. Governments should take more serious steps toward reducing healthcare inequalities, especially in terms of maternal and infant health.